FRANCHISING AS A STRATEGY FOR HOTEL CHAINS EXPANSION ON A GLOBAL LEVEL - Gašević, Dragana Lj; Stanković, Milica (International Journal of Economic Practice and Policy, 2016)
Franchising (franchise business model) has been successfully implemented by companies in the tourism industry for many years. Considering all its specific features, in particular characteristics that are related to the hotel industry, the aim of this study is to present the role and importance of this business model in tourism industry. Presenting examples of franchise business application in InterContinental and Marriott International hospitality groups, this paper underlines the benefits of this business model for all participants. Especially important is the dimension that goes in favor of tourists (consumers of tourism servicies) whose choice of hotels within the famous franchise system can reduce or totally eliminate the risk of making a wrong decision. Furthermore, their choice of a well-known brand is a guarantee of a positive experience for them. The empirical data presented in this paper show that the franchising is dominant form of hotel chains expansion on a global level.